Internalisasi Sila Ketuhanan Yang Maha Esa dalam Kehidupan Rohani STKIP Citra Bakti (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This article examines the internalization of the principle of Belief in the One Almighty God in spiritual life at the STKIP Citra Bakti Campus. The study aims to identify how to develop the principle of Belief in the One Almighty God in spiritual life at the STKIP Citra Bakti Campus. The research method uses a descriptive qualitative approach with a literature study technique. The results of the study indicate that the internalization of the value of Belief in the One Almighty God plays an important role in shaping the character and spirituality of students. These values ​​are reflected in the practice of tolerance between religious communities, respect for differences in beliefs, and acceptance of religious teachings that prioritize good morality and ethics. This study is expected to contribute to the development of character education based on divine values ​​in the daily lives of students. Based on the results of this study, it can be concluded that the internalization of the principle of Belief in the One Almighty God in the spiritual life of students at STKIP Citra Bakti is going quite well. The majority of students have a good understanding of the principle of Belief in the One Almighty God and strive to practice it in their daily lives. Participation in religious activities is also quite high, although there are challenges related to managing time to balance academic and spiritual activities.